Doença do nível adjacente após artrodese da coluna lombar - Filipe, Fernando Manuel Rana (2006)
Adjacent segment disease is defined as an abnormal process developing in the adjacent level above and/or bellow the arthrodesis of the segment. It is considered a late complication of lumbar spine arthrodesis. It has been very important due to the procedures in the last years. Objective: To evaluate the risk factors associated with the disease at adjacent level as well as its relationship with the natural history of degenerative disease of the lumbar spine. Material and Methods: This was a retrospective study, from January 2000 to December 2002.Thirty-eight patients undergoing arthrodesis in the lumbosacral spine using the pedicle screw fixation participated in the study. Results: These patients had a mean follow-up of 30 months; 10 patients presented adjacent segment disease, 7 disc degeneration, 2 spinal stenosis and one discal spine hernia. The patients´ mean age was 48.5 years; female sex was the majority. Degeneration occurred in 4 patients with stenosis; 4 with spondylolisthesis, and 1 with post disc hernia; all these had been submitted to arthrodesis of lumbosacral spine. The majority was asymptomatic, after being treated by arthrodesis in multiple levels. There was no statistical difference when the above factors were related. Conclusion: Adjacent segment disease is a late complication in the arthrodesis of lumbosacral spine with no relationship of risk factors presented in this study. Therefore, its origin could be related with the natural history of the degenerative disease of lumbar spine.